Occupational-Based Intervention Meningkatkan Fungsi Muskuloskeletal dan Occupational Performance Pasien Fraktur Ekstremitas Atas Post ORIF - Hendri Kurniawan; Fania Ayu Maharani (Jurnal Terapi Wicara dan Bahasa, 2026)
Background: Post-surgery, patients with upper extremity fractures often experience limited joint range of motion and muscle strength, which impacts occupational performance. Occupational-Based Intervention (OBI) integrates meaningful activities into patients' daily lives as part of the rehabilitation process. Objectives: This study aims to determine the effect of Occupational-Based Intervention on musculoskeletal function and occupational performance of patients with upper extremity fractures after open reduction internal fixation (ORIF). Methods: The study used a quasi-experimental design. The study was conducted at the Occupational Therapy Unit of RSUD. Wonosari Gunungkidul. A sample of 35 people (25 in the intervention group and 10 in the control group) was obtained using a purposive sampling technique. Research variables were measured using a goniometer, manual muscle strength tests, and the Canadian occupational performance measure (COPM). Research data were analyzed using the Wilcoxon signed-rank test, Mann-Whitney test, and Cohen's d test using SPSS version 25. Results: The majority of the study subjects were male (60%), had a radius fracture (42.86%), and had difficulty dressing (25.71%). The results of the paired comparison test of data on range of motion, muscle strength, and occupational performance in the treatment and control groups showed p <0.05. The results of the comparison test of data on changes in range of motion and muscle strength between groups were not significant (p>0.05), but changes in occupational performance were significant (p<0.05). The results of the Cohen's test showed low intervention effectiveness (d<0.5) on LGS and muscle strength in both groups, as well as occupational performance in the control group. The effectiveness of the intervention on occupational performance in the treatment group was categorized as moderate (d≤0.5). Conclusion: Occupational-Based Intervention (OBI) significantly improves musculoskeletal function (joint range of motion and muscle strength) and occupational performance in patients with upper extremity fractures after ORIF. OBI is more effective in improving occupational performance (performance and satisfaction) than biomechanical approaches. Keywords: Fracture, Musculoskeletal, Occupational, Performance.